Experimental and Numerical simulation of Heat and Mass Transfer along with Stresses in Fruits - S C Managuli, Aswath, H M Sathish, K N Seetharamu (International Journal of Advanced Science and Technology, 2020)
Heat and mass transfer analysis of fruit is complex process where it involves physical property change and shrinkage of material which occurs simultaneously. Food drying is a process of removing moisture to preserve fruits by preventing microbial spoilage in which it increase shelf life of the product. In this work, a governing differential equation for heat and mass transfer is taken from literature and thermal properties of watermelon along with the boundary condition is incorporated in COMSOL Multiphysics 5.3a software to get plots for various time interval. The extension of study is made by analyzing the Von-mises stress, total displacement, and deformation of the watermelon during drying process. Numerical results were compared with the experimental results. The results holds good for all the time interval with good agreement. The developed simulation model helps to predict the change in shapes/dimensions of watermelon for environmental conditions during storage and as well as transportation. This prediction of results will be helpful in maintaining the ambient conditions and preserve the food quality. The preservation as result of depression of water activity leads to decrease in volume and weight.